2022
DOI: 10.36082/jdht.v3i2.661
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF A DECOCTION OF STAR FRUIT LEAVES (AVERRRHOA BILIMBI LINN) ON SALIVA pH

Abstract: Caries is characterized by the demineralization of enamel and dentin minerals, followed by the destruction of organic materials. Efforts that can be made to prevent tooth decay include consuming foods that contain flavonoids which are antioxidants. The pharmacological content of star fruit leaves are flavonoids, tannins, saponins, and potassium citrate. This study aims to determine the effect before and after gargling using a decoction of star fruit leaves (Averrhoa bilimbi linn). This study used quasi-experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…17 Based on a study by Restuning et al, the bilimbi leaves boiled water could also increase saliva pH (6.73). 16 Some studies reported that Galla chinensis, a Chinese herb, could be applied as a teeth remineralization agent due to its remineralization ability and antibacterial effect. [18][19][20][21] Zhang et al stated that the chemical components of Galla chinensis could induce enamel caries remineralization in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Based on a study by Restuning et al, the bilimbi leaves boiled water could also increase saliva pH (6.73). 16 Some studies reported that Galla chinensis, a Chinese herb, could be applied as a teeth remineralization agent due to its remineralization ability and antibacterial effect. [18][19][20][21] Zhang et al stated that the chemical components of Galla chinensis could induce enamel caries remineralization in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, bilimbi ( Averrhoa bilimbi ) was found to generate a remineralization effect, antibacterial effect, and increase saliva pH; therefore, it can be used as a teeth remineralization agent. 15 16 17 According to Abidin and Nainggolan, Averrhoa bilimbi extract yielded significant effects in the enamel remineralization and produced an enamel layer with smaller porous in demineralized teeth. The study also reported that the combination of Averrhoa bilimbi extract and CPP-ACP induced enamel remineralization closer to normal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation